Variabilidade e progresso genético com seleção recorrente em arroz de terras altas - Morais Júnior, Odilon Peixoto de (2013)
Rice (Oryza sativa L.) is the most important cereal in the world as a major component of the staple food of the world’s population. The increase of the yield potential of new upland rice cultivars has been became highlighted as a main challenge for the plant breeding in this millennium. The increasing mean yield of cultivars becomes more difficult to identify superior genotypes, because the contrasts among elite-lines are becoming smaller. This highlights the importance of developing improved populations with high frequency of favorable alleles and genetic variability. The recurrent selection is a method based on population breeding and the main characteristic is obtaining long-term results. Using the recurrent selection population CNA6 of upland rice, the objectives of this study were: (i) to obtain estimates of genetic and phenotypic parameters among S0:2 progenies for grain yield (PG, in kg ha-1) and plant height (AP, in cm), in four selection cycles; (ii) to determine the influence of the progeny x location interaction on estimates of genetic and phenotypic parameters; (iii) to estimate the genetic progress of the population along the four cycles of recurrent selection for PG, AP and days-to-flowering (DF, in days); and (iv) to evaluate the genetic potential of this population through the expected proportion of superior lines after each selection cycle. It was used the data set from yield trials of S0:2 progenies in the years 2000/01, 2003/04, 2006/07 and 2009/10 from Brazilian Agricultural Research Corporation (Embrapa). In each cycle, the trials were carried out in some locations (Santo Antônio de Goiás-GO; Paragominas-PA; Primavera do Leste, MT; Sinop-MT; Teresina-PI and Vilhena-RO). The experimental design was augmented block of Federer, without replicate within location and with at least three checks. The plots were composed by four rows with five meters long, spacing of 0.30 m, and density of 60 seeds per meter. In each cycle, the data set from PG and AP were subjected to individual analysis of variance for Santo Antônio de Goiás-GO, the unique common location in all cycles, and joint analysis of variance for all locations. Estimates of phenotypic, genotypic and environment correlations among three traits studied was obtained. The average gains per cycle, and average annual gains and total were estimated, as also the weighted coefficients of determination and gains among cycles and the total gain based on contrasts among estimated averages for each cycle. In addition, the expected proportions of superior inbred lines after each selection cycle were obtained, using the average of the checks as standard. Estimates of genetic correlations between PG and AP were -0.42 and between AP and DF the -0.11 , both significant (p0,01), and no correlation was detected among PG and DF. Thus, within this population progenies with higher grain yield had lower plant height, and cycle may be early, medium or late. Estimates of genetic variance among S0:2 progenies suggested that genetic variability was maintained along the cycles of selection for the traits PG and AP. After unfolding of the genotype x location interaction (GxL) was observed predominance of the crossover interaction for PG and AP. Finally, it was found that the GxL interaction affected the estimates of genetic and phenotypic parameters for both traits, due to the wide geographic distribution of the target environments, which the recurrent selection program aims to obtain genetic gains in medium and long term. The results show clearly the efficiency of recurrent selection program in the progress of the population mean for grain yield and plant height, with significant genetic gains observed during the four cycles of selection. The genetic potential of the population to develop superior inbred lines increased during to selection cycles for grain yield and plant height. Despite the absence of genetic gain for days-to-flowering, the genetic potential for this trait was kept in the population during the four cycles elapsed.